1991
DOI: 10.1139/z91-267
|View full text |Cite
|
Sign up to set email alerts
|

A daily cycle of apocrine secretion by the B cells in the hepatopancreas of terrestrial isopods

Abstract: The ultrastructure of the two cell types of the hepatopancreas of the terrestrial isopods Oniscus asellus and Porcellio scaber was examined at hourly intervals in animals habituated to a 16 h light: 8 h dark cycle. The ultrastructure of the B cells undergoes substantial changes which are repeated every 24 h. This 'B cell cycle' can be divided into two stages. During the first, 'extrusive' stage, which begins about 1 h before the onset of the light period, the contents of the B cells apical to the nuclei are vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 7 publications
7
41
2
Order By: Relevance
“…The animals can eliminate the assimilated lead to about 50%, but after 2}4 weeks of feeding on uncontaminated litter the decline ceased (see Witzel, 1998). According to the histochemical "ndings of, e.g., Hopkin and Martin (1982b) and Hames and Hopkin (1991a) were not signi"cantly in#uenced by the presence of zinc, although there were di!erences in the lead content in the di!erent experiments. But this e!ect was more likely caused by di!erences in the weight of the animals.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The animals can eliminate the assimilated lead to about 50%, but after 2}4 weeks of feeding on uncontaminated litter the decline ceased (see Witzel, 1998). According to the histochemical "ndings of, e.g., Hopkin and Martin (1982b) and Hames and Hopkin (1991a) were not signi"cantly in#uenced by the presence of zinc, although there were di!erences in the lead content in the di!erent experiments. But this e!ect was more likely caused by di!erences in the weight of the animals.…”
Section: Discussionmentioning
confidence: 85%
“…B cells have secretory function and void cell material in a 24-h rhythm into the lumen of the hepatopancreas, whereas S cells have only a storage function and never void any material. Thus metals that are stored in the granules of S cells remain in the body until the death of the animal (Hames and Hopkin, 1991a). Although there seems to be no point for further discussion contradictory statements have been made about the ability of P. scaber to eliminate cadmium.…”
Section: Introductionmentioning
confidence: 99%
“…The hepatopancreas of isopods is composed of small (S) and big (B) cells, whose functions are absorption and absorption/secretion, respectively [44].…”
Section: Zinc Body Contentmentioning
confidence: 99%
“…It has been shown that zinc will form granules in both B and S cells of P. scaber [44]. However, the capacity to excrete metals is speciesdependent [46].…”
Section: Zinc Body Contentmentioning
confidence: 99%
“…But Hopkin et al (1985a) have shown that the copper level in intermolt animals is too high to allow for massive copper loss during molting. Furthermore, the cells containing the copper granules (S-cells) do not undergo a daily cycle (Hames and Hopkin, 1990) and never void their contents into the lumen of the hepatopancreas (Hopkin, 1990). Consequently, the vast majority of metals stored in these copper-containing granules remains within the epithelium until the isopod dies.…”
Section: Woodlice (Isopoda)mentioning
confidence: 99%